5+10(-10x-9)=-3

Simple and best practice solution for 5+10(-10x-9)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+10(-10x-9)=-3 equation:


Simplifying
5 + 10(-10x + -9) = -3

Reorder the terms:
5 + 10(-9 + -10x) = -3
5 + (-9 * 10 + -10x * 10) = -3
5 + (-90 + -100x) = -3

Combine like terms: 5 + -90 = -85
-85 + -100x = -3

Solving
-85 + -100x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '85' to each side of the equation.
-85 + 85 + -100x = -3 + 85

Combine like terms: -85 + 85 = 0
0 + -100x = -3 + 85
-100x = -3 + 85

Combine like terms: -3 + 85 = 82
-100x = 82

Divide each side by '-100'.
x = -0.82

Simplifying
x = -0.82

See similar equations:

| 2/5=4/5(c) | | 6cos(6x)sin(7y)=7 | | Cos(2x)-cos(4x)=o | | 44x+2+90=180 | | 48/(-8) | | 4(2y+4)=3(y-6) | | -28=4/5(d) | | 4+11x=-40 | | x+57+x+137=180 | | 6x+11y-10x-8y+9x-7y= | | 4+5(-3x+7)=-9 | | (.1-x)*(.2-x)= | | 48/(-18) | | 50-8x=-6 | | 26+(2y+1)= | | -2=8y+3(y+3) | | (7x-4)(3x+9)=0 | | (x+2)(5x+6)=0 | | -10x+10=-40 | | -5.2(4s+6)-1.7(2s-4)= | | 3(2x+15)=2x+20 | | -5-8x=5 | | 2.8x+1y=747.7 | | 2(x-4)=42 | | -100x-300=300 | | 3z+8=-2z+13 | | c(c-5)=0 | | 27=3/4(y) | | s^3+2s^2-25s=50 | | 6[5-(4x-4)]+7x=0 | | 4w+7=7w-14 | | 3x^2+26x+73=0 |

Equations solver categories